Charlie & Mouse outdoors - Snyder, Laurel; Hughes, Emily (Emily M.) (Chronicle Books, 2020)
Charlie and Mouse and their parents are going on a camping trip, and there will be hiking, storytelling, marshmallows, and campfires, and the joy that comes from sharing it all.
390L
Decoding demand: 57 (medium) Semantic demand: 63 (high) Syntactic demand: 43 (medium) Structure demand: 66 (high)
Accelerated Reader AR
Keywords: Brothers -- Juvenile fiction; Camping -- Juvenile fiction; Families -- Juvenile fiction; Brothers -- Fiction; Camping -- Fiction; Family life -- Fiction